Large-capacity optical path cross-connect system for WDM photonic transport network. - Koga, M. (IEEE Journal on selected areas in communications)
This paper demonstrates our previously developed large-capacity optical path cross-connect (OPXC) system. The major hurdles to be cleared are (1) establishment of a highly modular architecture that facilitates hardware design and upgrading and (2) the development of an OPXC demonstrator designed to achieve 320-Gbit/s throughput capacity. Due to the use of planar lightwave circuit technologies, compact size packaging for an 8×16 delivery-and-coupling type optical switch and an arrayed-waveguide grating for a wavelength-demultiplexer are achieved. The dense packaging of the four-channel optical regenerators (3-R function regenerator) makes it possible to realize a large-capacity OPXC that can offer high quality transmission and ensure robustness in terms of multiple node connection. Performance test results confirm the validity of the system design and the feasibility of 320-Gbit/s OPXC implementation